Morphology and morphometry of proximal dry radii in south coastal population - Rajasree, Gali; Sucharitha, Todimaldinnae; Karuppiah, Devi Sankar; Hema, Lattupalli (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2016)
Knowledge of the size and shape of radial head is essential for construction of radial head prosthesis. Further, the measurements of bicipital tuberosity and its angular relationship to radial head are significant in surgical techniques, like in the reconstruction of biceps tendon. Even the morphometry of the distal radius is significant in numerous clinical orthopedic situations such as reduction of distal radius fractures and in the design of distal radius prosthesis. So, the aim of the study was to determine the morphometric parameters of proximal and distal radius in dry adult Indian radius.